Kajian Kinerja Kebijakan Program Agropolitan di Kecamatan Sumowono dan Kecamatan Bandungan Kabupaten Semarang - Florence Kristianti Siahaan; Mohammad Muktiali (Jurusan Perencanaan Wilayah dan Kota, 2022)
Sumowono and Bandungan sub-districts are parts of Semarang Regency which are designated as one of the rural developments through the agropolitan concept. The agropolitan program was established in 2003 with the aim of improving the welfare and standard of living of the community. In practice, conditions for agropolitan programs in the region are not developing optimally or are stagnant. This was conveyed according to the Central Java Province Regional Planning and Development Agency. Then, based on the report from Bappeda of Central Java Province, it shows that the agropolitan development of Semarang Regency is lagging behind that of Pemalang, Temanggung, Magelang, Brebes, Purworejo, and Karanganyar Regencies. This is because agropolitan activities only focus on land production activities (on farm). Seeing the stagnant agropolitan development, a review of the performance of agropolitan program policies was conducted in Sumowono and Bandungan districts. This study aims to examine the performance of policies in the agropolitan system in Sumowono and Bandungan districts. The results of the analysis above, it can be seen that the performance of the agropolitan program in Sumowono and Bandungan districts is in the quite successful category. This can be seen from the downstream agribusiness subsystem in the two districts which is included in the low category. The downstream agribusiness subsystem score in Sumowono District was 45.09 and Bandungan District was 49.03. This is because the knowledge and skills of farmer groups in utilizing technology for promotion and preservation are still low and marketing reach is still at the provincial level. Thus, the competitiveness of agricultural production in Sumowono and Bandungan Districts is still low.